2010
DOI: 10.1038/onc.2010.230
|View full text |Cite
|
Sign up to set email alerts
|

L1CAM–integrin interaction induces constitutive NF-κB activation in pancreatic adenocarcinoma cells by enhancing IL-1β expression

Abstract: L1 cell adhesion molecule (L1CAM) overexpression is often associated with bad prognosis in various human carcinomas. Recent studies also suggest a role of L1CAM in pancreatic ductal adenocarcinomas (PDAC). To further address its contribution, we expressed functional domains of L1CAM in PT45-P1 PDAC cells. We found that L1CAM that is full length (L1-FL), but neither the soluble ectodomain (L1ecto) nor the cytoplasmic part (L1cyt), could enhance cell proliferation or tumour growth in mice. Expression of L1-FL re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 48 publications
6
49
0
Order By: Relevance
“…Our data show that L1CAM suppression in H460 and H125 cells reduces tumor growth rate in SCID mice, which can be rescued by restoring L1CAM levels. A role for L1CAM in the tumorigenicity of NSCLC cells is consistent with studies in other cancer cell types, as overexpression of L1CAM in ovarian (34), colon (43), and pancreatic cancer cells (44) augments tumor growth in mice. In addition, biweekly intraperitoneal injection of a monoclonal L1CAM antibody (chCE7) in ovarian carcinoma-bearing mice led to significant reduction of tumor burden (45).…”
Section: Discussionsupporting
confidence: 79%
“…Our data show that L1CAM suppression in H460 and H125 cells reduces tumor growth rate in SCID mice, which can be rescued by restoring L1CAM levels. A role for L1CAM in the tumorigenicity of NSCLC cells is consistent with studies in other cancer cell types, as overexpression of L1CAM in ovarian (34), colon (43), and pancreatic cancer cells (44) augments tumor growth in mice. In addition, biweekly intraperitoneal injection of a monoclonal L1CAM antibody (chCE7) in ovarian carcinoma-bearing mice led to significant reduction of tumor burden (45).…”
Section: Discussionsupporting
confidence: 79%
“…Remarkably, this phenotype was mostly rescued by silencing of L1CAM. Taken together, the data suggest that core fucosylation enhances the ability of L1CAM to promote metastasis, altering either L1CAM activity or interactions with its counterparts (Kiefel et al, 2010). …”
Section: Discussionmentioning
confidence: 87%
“…A recent study showed that NF-kB is also induced by L1 in pancreatic ductal carcinoma cells (26). The forced expression of L1 (in Ls174T and HCT116), or the shRNA-mediated suppression of endogenous L1 in SW620 CRC cells that had profound effects on the tumorigenic capacity of these cells (9), was not associated with changes in the expression and organization of E-cadherin.…”
Section: Discussionmentioning
confidence: 98%